Impact of Conservation Tillage Technology Application on Farmers’ Technical Efficiency: Evidence from China - Chenguang Teng; Kaiyu Lyu; Mengshuai Zhu; Chongshang Zhang (Agriculture, 2023)
Conservation tillage plays a crucial role in preventing soil erosion, improving soil quality, and encouraging sustainable agriculture. This study analyzes the effects of conservation tillage on farmers’ technical efficiency and its underlying mechanisms, using a sample of 853 households and 1706 land plots from China’s Jilin, Sichuan, Jiangsu, and Henan provinces. The results indicate that conservation tillage can enhance technical efficiency, resulting in an average increase of 0.022 units, The study further demonstrates that conservation tillage technology primarily enhances technical efficiency by increasing output and reducing production costs. This study proposes policy recommendations for promoting the use of conservation tillage technology to enhance farmers’ technical efficiency.